Inhibition of autophagy by 3-MA potentiates purvalanol-induced apoptosis in Bax deficient HCT 116 colon cancer cells - Çoker Gürkan, Ajda; Güvenir, Esin; Palavan Unsal, Narçin; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Elsevier Inc, 525 B Street, Ste 1900, San Diego, Ca 92101-4495 Usa, 2014)
The purine-derived analogs, roscovitine and purvalanol are selective synthetic inhibitors of cyclin-dependent kinases (CDKs) induced cell cycle arrest and lead to apoptotic cell death in various cancer cells. Although a number of studies investigated the molecular mechanism of each CDK inhibitor on apoptotic cell death mechanism with their therapeutic potential, their regulatory role on autophagy is not clarified yet. In this paper, our aim was to investigate molecular mechanism of CDK inhibitors on autophagy and apoptosis in wild type (wt) and Bax deficient HCT 116 cells. Exposure of HCT 116 wt and Bax(-/-) cells to roscovitine or purvalanol for 24 h decreased cell viability in dose-dependent manner. However, Bax deficient HCT 116 cells were found more resistant against purvalanol treatment compared to wt cells. We also established that both CDK inhibitors induced apoptosis through activating mitochondria-mediated pathway in caspase-dependent manner regardless of Bax expression in HCT 116 colon cancer cells. Concomitantly, we determined that purvalanol was also effective on autophagy in HCT 116 colon cancer cells. Inhibition of autophagy by 3-MA treatment enhanced the purvalanol induced apoptotic cell death in HCT 116 Bax(-/-) cells. Our results revealed that mechanistic action of each CDK inhibitor on cell death mechanism differs. While purvalanol treatment activated apoptosis and autophagy in HCT 116 cells, roscovitine was only effective on caspase-dependent apoptotic pathway. Another important difference between two CDK inhibitors, although roscovitine treatment overcame Bax-mediated drug resistance in HCT 116 cells, purvalanol did not exert same effect. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Colon cancer; Apoptosis; Autophagy; CDK inhibitors; Bax; Cyclin-Dependent Kinases; Carcinoma-Cells; In-Vitro; Roscovitine; Death; Macroautophagy; Olomoucine; Proteins; Pathway; Stress